La fabrique des héros. Usages politiques de Francisco Morazán en Amérique Centrale au XXe siècle (1942-1992) - Catherine Lacaze (Conserveries Mémorielles)
This article focuses on the memory of Francisco Morazán, a Honduran liberal caudillo who has been president of the Federal Republic of Central America during the 1830s. After showing how the historic person evolved as a hero during the century following his death in 1842. Then we analyse the 1942 commemoration and finally we describe the changes in the political uses of the figure until the bicentenary of his birth in 1992. The objective is here to determining to what extent the cult of Morazán became more popular during the XXth century, putting emphasis on a comparative perspective at the Central America scale (Guatemala, El Salvador, Honduras, Nicaragua and Costa Rica).